Role Of Marketing Strategies In Increasing Company Competitiveness: Role Of Marketing Strategies In Increasing Company Competitiveness - Gulchehra, Narzullayeva (Центр Научных Публикаций (buxdu.uz), 2021)
Abstract: The article analyzes the main competitive strategies. Competitive strategy provides executives with the practical knowledge, new skills, and tools to turn strategic ideas into action. Competitive research is an area of strategic research that specializes in gathering information about competing firms. This is an important tactic for figuring out what competitors are doing and what threat they pose to your financial strength.